1978
DOI: 10.1080/00022470.1978.10470652
|View full text |Cite
|
Sign up to set email alerts
|

Revised Weighting of CVS/CH Test Results for CO Vehicle Emission Factors

Abstract: APCA NOTE-BOOKat 10 to 15 min after the dust feed system was turned on. Extremely large fluctuations in the screen current are evidence of a high level of back corona activity.The notation Q/m on Figure 2 indicates the interval of time during which a measurement of particle charging effectiveness was made. Particles were collected on a silver mesh filter mounted in a plastic filter holder, fitted with a nozzle for isokinetic sampling. The filter was connected to an electrometer so that the charge accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1980
1980

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In a previous publication 10 it was suggested that urban center CO air quality after 1974 would improve faster than predictions based on current FTP emission factors because of the introduction of catalyst equipped LDV's. This conclusion was based on an analysis made with GRM which showed that FTP overestimates the contribution of cold start emissions to urban-center CO air quality (8-hr average).…”
Section: Cold Start Emissionsmentioning
confidence: 99%
“…In a previous publication 10 it was suggested that urban center CO air quality after 1974 would improve faster than predictions based on current FTP emission factors because of the introduction of catalyst equipped LDV's. This conclusion was based on an analysis made with GRM which showed that FTP overestimates the contribution of cold start emissions to urban-center CO air quality (8-hr average).…”
Section: Cold Start Emissionsmentioning
confidence: 99%